オクヒョウガ ガン シラセ ヒョウガ ジョウコ ノ サイヒョウ チョウサ - 西尾, 文彦; ニシオ, フミヒコ; 内藤, 靖彦; ナイトウ, ヤスヒコ; 岩波, 圭祐; イワナミ, ケイスケ; 二ツ町, 悟; フタツマチ, サトル; Nishio, Fumihiko; Naito, Yasuhiko; Iwanami, Keisuke; Futatsumachi, Satoru (1984)
P(論文) 白瀬氷河の右岸(東側)の奥氷河岩の近くに1962年1月以来空中写真によって氷河上湖がほぼ同じ位置に確認されている。湖の成因および湖水が海とつながっているかどうかを調べるために, 1984年1月, 湖の地形調査および採水調査を行った。湖の大きさは, 長さ2700m, 幅360mで, 湖水面の高度は56-65m, 湖底面は海抜16-25mで海水面より高いことが明らかになった。湖水は電気伝導度の測定結果から, 周辺の融雪水または融氷水であることが明らかになった。湖は流速の大きい白瀬氷河と湖の東側の基盤の盛り上がりによる流速の小さい氷流の間の強い剪断力によってクレバスが形成され, 融雪(氷)水が溜って湖に拡大したと推定される。 On the east side of the Shirase Glacier near the Oku-hyoga Rock, the supraglacial lake has been observed nearly at the same position since January 1962. The lake is 2700m long and 360m wide. The elevation of the lake's surface was measured by altimeter between 56 and 65m above sea level and of the bottom of the lake is 16 to 25m above sea level. The lake water was collected and the specific conductivity of it was measured. The composition of the lake water shows the melted snow or ice, not the sea water. Therefore, the bottom of the lake might not be connected with the sea. The lake may have been formed by a fissure on the glacier ice resulting from the strong shear stresses between the west side of fast moving glacier ice mass in the Shirase Glacier and the east side of ice mass obstructed by the subglacial topography. departmental bulletin paper